2010
DOI: 10.1111/j.1365-2796.2010.02280.x
|View full text |Cite|
|
Sign up to set email alerts
|

No survival benefit from early-start dialysis in a population-based, inception cohort study of Swedish patients with chronic kidney disease

Abstract: Abstract. Evans M., Tettamanti G., Nyrén O., Bellocco R., Fored C.M., Elinder C.-G. (Karolinska Institutet and Karolinska University Hospital, Stockholm, Sweden; Karolinska Institutet, Stockholm, Sweden; University of Milano-Bicocca, Milan, Italy; Karolinska Institutet, Stockholm, Sweden) No survival benefit from early-start dialysis in a population-based, inception cohort study of Swedish patients with chronic kidney disease. J Intern Med 2011; 269: 289-298.Objective. To investigate how the timing of dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
3
50
0
Order By: Relevance
“…The main concern of observational studies including ours is the difference between the clinical characteristics and dialysis indications of the early and late initiation groups. Patients with early dialysis initiation were more likely to be men and diabetic, have severe heart failure or coronary heart disease, are less likely to have glomerulonephritis or polycystic kidney disease and have lower serum albumin level and more comorbidity and in summary, they are sicker patients [5,9,14,17]. In our DAGL patients, we found similar results.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The main concern of observational studies including ours is the difference between the clinical characteristics and dialysis indications of the early and late initiation groups. Patients with early dialysis initiation were more likely to be men and diabetic, have severe heart failure or coronary heart disease, are less likely to have glomerulonephritis or polycystic kidney disease and have lower serum albumin level and more comorbidity and in summary, they are sicker patients [5,9,14,17]. In our DAGL patients, we found similar results.…”
Section: Discussionsupporting
confidence: 78%
“…Despite the weak evidence, early initiation was accepted and it was common practice until recently. More recent studies, including a randomized controlled trial, did not support early initiation of dialysis in CKD patients [5,8,9,12,[15][16][17][18]. The large multicenter trial from Netherland, the Netherlands Cooperative Study on the Adequacy of Dialysis, was the first observational study which casts doubt on the advantages of early dialysis initiation [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several retrospective studies suggest that dialysis initiation with eGFR,5 ml/min per 1.73 m 2 is associated with lower mortality than higher eGFR dialysis starts (69)(70)(71)(72), although such studies are limited by survival bias, confounding by indication, and other issues. At least one prospective cohort study, however, found a significantly higher mortality (hazard ratio, 4.65; 95% confidence interval, 2.28-9.49) among patients not yet on dialysis with eGFR,7.5 ml/ min per 1.73 m 2 (73). A recent Canadian clinical practice guideline recommends deferring dialysis until the eGFR is 6 ml/min per 1.73 m 2 (74), whereas another indicates that clinical indications for starting dialysis "often but not invariably" occur when eGFR is 5-10 ml/min per 1.73 m 2 (2).…”
Section: Answermentioning
confidence: 99%